SAT0756-HPR Effect of nsaid intake on kinesiophobia in patients with ankylosing spondylitis. (15th June 2017) - Kinikli, GI; Karahan, S; Ates, A; Turgay, M; Kinikli, G
Abstract : Background: Spinal stiffness and loss of spinal mobility, explained byspinal inflammation and structural damage due to extensive osteoproliferation, are characteristics of Ankylosing Spondylitis (AS). AS usually disables a person with severe back pain and, in later stages, remarkable spinal kyphotic deformity.The deformity eventually may necessitate a major corrective procedure. Therefore, controlling the symptoms and progression of AS in early stages by effective medication is the main step in the management of AS. Objectives: The aim of this study was to investigate the effectiveness of DMARD therapies on NSAID intake and kinesiophobia in patients with AS. Methods: A total of 74 patients, diagnosed according to the modified New York criteria for AS, were enrolled. Patients were assessed to measure disease activity using the Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]. Fear of movement was assessed with the Tampa Scale for Kinesiophobia [TSK]. To calculate NSAID intake and the type of NSAID, dose, percentage of days with intake were recorded, along with DMARD therapy, age, body mass index (BMI), and disease duration. The NSAID equivalent scoring was calculated according to recommendations from longitudinal clinical studies. The drug therapy groups were compared using the Kruskal-Wallis test and the Chi-square test. Correlation analysis was evaluated by Spearman's correlation coefficient. Results: Seventy-four patients (36 women, 38 men; mean age: 43.81±10.18 years; mean disease duration: 9.89±8.50 years; BMI: 28.20±5.07) treated with four types of DMARDs (adalimumab+golimumab =17; infliximab =19; etanercept =13; sulfasalazine =25) were included. There were no drug group differences in terms of age (p=0.179), sex (p=0.886), or BMI (p=0.821). BASDAI scores (mean: 3.9±2.4) and NSAID intake (mean: 68.1±76.1; p=0.003) were significantly higher in the sulfasalazine therapy (ST) group compared to other drug groups. BASDAI scores were not correlated with age (p=0.103), disease duration (p=0.131), BMI (p=0.641) or the TSK scores (p=0.376). Different NSAID intake groups (p=0.089) had similar TSK scores. Conclusions: Patients with AS had fear of movement independent of age, BMI or disease duration, even when they experienced positive results from drug therapies and concomitant therapy with a single oral dose of NSAID or oral corticosteroids in stable dosages. References: Braun J, Baraliakos X, Heldmann F, et al. Tumor necrosis factor alpha antagonists in the treatment of axial spondyloarthritis. Expert Opin Investig Drugs. 2014;23:647–659. Rohekar S, Chan J, Tse SM, et al. 2014 update of the Canadian Rheumatology Association/Spondyloarthritis Research Consortium of Canada treatment recommendations for the management of spondy- loarthritis. Part I: principles of the management of spondyloarthritis in Canada. J Rheumatol. 2015;42:654–664. Rohekar S, Chan J, Tse SM, et al. 2014 update of the Canadian Rheumatology Association/Spondyloarthritis Research Consortium of Canada treatment recommendations for the management of spondy- loarthritis. Part II: specific management recommendations. J Rheu- matol. 2015;42:665–681. Acknowledgements: We would like to thank Rheumatology Nurse Ayten Yuksek in our department for monitoring and documenting of the data, and our patients for assistance with their valuable participation to our study. Disclosure of Interest: None declared